2008
DOI: 10.4103/0971-9261.44761
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendicitis score: A retrospective analysis

Abstract: Aims:Evaluation of the pediatric appendicitis score (PAS), in all patients who had an appendicectomy over a one-year period.Methods:Retrospective study of 56 patients aged 4–15 years, who underwent an emergency appendicectomy. PAS was applied and patients were divided according to the PAS protocol into high probability and low probability groups. These results were then correlated with histology.Results:The PAS had sensitivity 0.87, specificity 0.59, positive predictive value 0.83, and negative predictive valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
9
1
1
Order By: Relevance
“…Management of children diagnosed of acute appendicitis involves a number of protocols which is mainly subject to the level of complications involved at the time certainty was established. Typically, children suspected of having acute appendicitis are immediately placed on admission for a close or active monitoring and clinical examinations in addition to scoring systems depending on the myriad of the symptoms presented so as to minimize misdiagnosis . Open appendectomy is the most common approach for children but advanced minimally invasive technique such as laparoscopy is now being introduced by skilled surgeons .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of children diagnosed of acute appendicitis involves a number of protocols which is mainly subject to the level of complications involved at the time certainty was established. Typically, children suspected of having acute appendicitis are immediately placed on admission for a close or active monitoring and clinical examinations in addition to scoring systems depending on the myriad of the symptoms presented so as to minimize misdiagnosis . Open appendectomy is the most common approach for children but advanced minimally invasive technique such as laparoscopy is now being introduced by skilled surgeons .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, children suspected of having acute appendicitis are immediately placed on admission for a close or active monitoring and clinical examinations in addition to scoring systems depending on the myriad of the symptoms presented so as to minimize misdiagnosis. 25,26 Open appendectomy is the most common approach for children but advanced minimally invasive technique such as laparoscopy is now being introduced by skilled surgeons. 27 Subsequent recuperation devoid of events with appropriate fluid resuscitation and antibiotic administration, a smooth and full recovery is the eventual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…When it was initially derived in 2002, the PAS showed a sensitivity of 100% and a specificity of 92% for acute appendicitis using a single cutoff of 6; however, several validation studies were unable to reproduce these test characteristics . Subsequently, improved sensitivity and specificity were found when two cutoffs were used, thereby dividing patients into high‐, moderate‐, and low‐risk clinical groups . For instance, for cutoffs of ≥7 the PAS specificity ranges from 82.4% to 98%, and for a cutoff of ≥8 of the PAS specificity ranges from 95.1% to 97.6% .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Goulder et al [17], in a study published in 2008, found that the PAS cannot be recommended as it would later lead to an unacceptable risk of high medical or surgical delays in up to 13% of patients with AA.…”
Section: Discussionmentioning
confidence: 99%